Synthesis and Characterization of Chitosan Based Interpenetrating Network Micro Gel for Controlled Release of Cephalexin - Shivashankar, Murugesh; Kumar Mandal, Badal; Himaja, M. (Asian Journal of Chemistry, 2012)
The aim of this study is to prepare pH-sensitive interpenetrating network micro gels based on chitosan and its grafted copolymer, hydrolyzed grafted copolymer (that are cross linked with glutaraldehyde by precipitation and cross linking methods) for the controlled release of cephalexin as model drug. The networks were characterized by Fourier transformed infrared spectroscopy, SEM, X-ray diffraction studies and swelling studies. All physical chemical characteristic are performed. The in vitro release is performed using phosphate buffer media (pH 2 and pH 7.4) and the release rate was controlled by tuning buffer pH. The results indicated that the networks could be potentially useful for controlled drug delivery. The extended release rates were observed from the conventional dosage release study which was more than 12 h.